Commentary: What Rural Education Research is of Most Worth? A Reply to Arnold, Newman, Gaddy, and Dean - Craig B. Howley; Paul Theobald; Aimee Howley (Journal of Research in Rural Education, 2005)
Offering a response to the question, "What rural education research is of most worth?", we recommend an approach very different from the one taken by Arnold, Newman, Gaddy, and Dean (2005) in their consideration of the rural education research literature. We remind readers that about 150 years ago, Herbert Spencer put a similar question""What is the knowledge of most worth?""to his readers, concluding that the answer was "science." We intend only light irony, however, acknowledging that the scientific spirit exerts strong influence on the project of scholarly research (for broad principles see, for instance, Shavelson & Towne, 2000). This influence is felt not only in hypothesis testing with mathematical tools, but also in historical, ethnographic, and other forms of research that rely more on analysis of language.